Empirical Analysis of Participation Patterns in Microfinancial Markets: The Cases of Ghana and Sri Lanka - Mirko Bendig (Peter Lang International Academic Publishers, 2012)
This book contributes to the empirical literature on households' participation in microfinancial services in developing countries. First, it estimates simultaneously the participation in microinsurance schemes and other financial services on household survey data from Ghana. Second, it analyzes the household's cumulative participation in microfinancial services using household survey data from Sri Lanka. Next, the study focuses on the question whether household's participation in micro life insurance in Sri Lanka is motivated by the desire to leave bequests. At last, it investigates different sequential steps of the household's microinsurance participation decision and the joint analysis of micro life and health insurance enrolment in Sri Lanka.
Keywords: 330